Penerapan Model Pembelajaran Problem Based Learning (PBL) untuk Meningkatkan Kemampuan Pemecahan Masalah Matematis Peserta Didik SMA Negeri 9 Surabaya - Risa Dewi Pramana; Anik Kirana; Fitria Indahwati (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2024)
In opportunity material, students' mathematical problem solving abilities are something that needs to be paid attention to. As a teacher, teachers should use various learning models that can help students improve their mathematical problem solving abilities. This research aims to help improve the mathematical problem solving abilities of class X-6 students at SMA Negeri 9 Surabaya through the Problem Based Learning (PBL) learning model on opportunity material. This research uses the Classroom Action Research (PTK) method which is divided into two cycles where each cycle consists of two meetings. The target subjects in this research were students in class X-6 of SMA Negeri 9 Surabaya, totaling 36 people. Data collection techniques in this research include observation and problem solving ability tests. From the data obtained, analysis was then carried out using descriptive analysis. The results obtained from this research are that students' mathematical problem solving abilities increase. In cycle one, there were 12 students who scored above the KKM (33.3%). Meanwhile, in cycle two, the number of students who scored above the KKM increased to 27 people (75%). Based on these results, the achievements of students who scored above the KKM increased so that students' mathematical problem solving abilities increased by 41.7% from cycle one to cycle two.